2017
DOI: 10.1021/acs.organomet.7b00541
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Diphenylacetylene Mediated by Rare-Earth Ferrocene Diamide Complexes

Abstract: The synthesis and characterization of Ln-C 4 Ph 4 -K, [(NN TBS )Ln(η 2 -C 4 Ph 4 )][K(THF) x ] (Ln = Sc, Y, Lu), rareearth metal complexes supported by a ferrocene diamide ligand, NN TBS (NN TBS = fc(NSi t BuMe 2 ) 2 , fc = 1,1′-ferrocenediyl), were accomplished. The preparation of the half-sandwich compounds, Ln-naph-K, [(NN TBS )Ln(μ-C 10 H 8 )][K(THF) 2 ] (Ln = Sc, Y, Lu, La), was necessary in order to obtain high yields of rare-earth metallacyclopentadienes. Unlike Y and Lu, La did not show the same reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 70 publications
(101 reference statements)
1
15
0
Order By: Relevance
“…4(2)°fold angle between the C3À Lu1À O1 and C3À C2À C1À O1 planes. The Lu1À C3 distance is 2.450(5) Å, which is comparable with the reported LuÀ C alkenyl distance, [11] but significantly longer than the LuÀ C bond length (2.276 Å) in 1.…”
Section: Resultssupporting
confidence: 78%
“…4(2)°fold angle between the C3À Lu1À O1 and C3À C2À C1À O1 planes. The Lu1À C3 distance is 2.450(5) Å, which is comparable with the reported LuÀ C alkenyl distance, [11] but significantly longer than the LuÀ C bond length (2.276 Å) in 1.…”
Section: Resultssupporting
confidence: 78%
“…It was suggested that both complexes are stabilized through the interaction of the scandium centers with the ferrocene backbone . A similar mono‐scandium reduced naphthalene complex [K{(NN fc )Sc}(μ‐C 10 H 8 )] was also proposed to form in solution, but due to thermal instability no spectroscopic or structural data were given . So far, there are no reports on any isolable mononuclear scandium complex of reduced arenes .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, rare‐earth complexes of cyclobutadienyl (Cb) ligands, [η 4 ‐C 4 R 4 ] 2− , are conspicuous by their absence, and only one actinide cyclobutadienyl complex is known . The paucity of f‐block cyclobutadienyl compounds is presumably due to the rarity of cyclobutadiene pro‐ligands, and the fact that rare‐earth elements have not yet been shown to mediate cyclobutadiene formation via alkyne cyclo‐dimerization …”
Section: Figurementioning
confidence: 99%
“…[9] The paucity of fblock cyclobutadienyl compounds is presumably due to the rarity of cyclobutadiene pro-ligands,a nd the fact that rareearth elements have not yet been shown to mediate cyclobutadiene formation via alkyne cyclo-dimerization. [10] With the aim of isolating the first rare-earth cyclobutadienyl complexes,w er easoned that as alt metathesis reaction betweena na lkali metals alt of 1,2,3,4-tetrakis(trimethylsilyl)cyclobuta-1,3-diene [11] and ar are-earth halide could furnish ac ompoundc ontaining the "squarocene" complex[ M{h 4 -C 4 (SiMe 3 ) 4 } 2 ] À .T hus,t he reaction of 1,2,3,4-tetrakis(trimethylsilyl)cyclobuta-1,3-diene with potassium metal in THF produced[ K 2 {h 4 -C 4 (SiMe 3 ) 4 }] (1)a sayellow powder in 72 %y ield. The 1 HNMR spectrum of 1 showedapeak at d = 0.45 ppm for the SiMe 3 substituents (Figures S1-S3,S upporting Information), and in the 13 C{ 1 H} NMR spectrum the cyclobutadienyl carbons occura td = 109.1 ppm and the SiMe 3 carbons at 5.6 ppm.…”
mentioning
confidence: 99%